Future directions for soundscape ecology: The importance of ornithological contributions. (14th December 2016) - Gasc, Amandine; Francomano, Dante; Dunning, John B.; Pijanowski, Bryan C.
Abstract: Building upon the rich legacies of bioacoustics and animal communication, soundscape ecology represents a new perspective through which ecologists can use the acoustic properties of ecosystems to understand the complex interactions of organisms, geophysical dynamics, and human activities. In this paper, we focus on the potential benefits of a soundscape approach for enhancing ornithological research and of ornithological perspectives for advancing the nascent field of soundscape ecology. We first summarize 4 major grounding principles of soundscape ecology in relation to avian ecology, evolution, and behavior. We then propose 3 research objectives that we envision as future directions for soundscape ecology: development of (1) soundscape metrics and interpretation, (2) understanding of soundscape drivers, and (3) soundscape-based disturbance indicators. Ornithological contributions can help advance the field of soundscape ecology to obtain these research objectives across various spatial, temporal, and organizational scales. Detailed ornithological knowledge can aid in the improvement of soundscape databases, interpretation of soundscape metrics, and validation of soundscape theories. Such contributions should also invite input from other taxonomic-group specialists, further enriching soundscape ecology. Reciprocally, soundscape approaches can enrich ornithology by offering an acoustic-based theoretical framework grounded in a broad ecological context, hosting soundscape collections from diverse ecosystems, and advancing acoustic methodologies. This paper is intended to stimulate further discussion and collaboration between ornithologists, soundscape ecologists, and any researchers studying sound in an ecological context in order to enhance research in these important domains of ecology.